Diplomasi Publik Indonesia Melalui Esport: Studi Kasus M4 World Championship 2023 - Listari Noviyanti (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
The development of esport has expanded beyond the entertainment industry and has increasingly become a strategic instrument in international relations, particularly in the practice of public diplomacy. Indonesia’s role as the host of the M4 World Championship 2023 represents a significant example of how esport events can be utilized to engage international audiences and project national roles. This study aims to analyze how Indonesia employed the M4 World Championship 2023 as a tool of public diplomacy. This research adopts a qualitative approach using a case study method. Data were collected from secondary sources through documentation and literature review, including official government publications, organizer reports, media coverage, and academic literature. The analytical framework is based on Nicholas J. Cull’s theory of public diplomacy, with a specific focus on the advocacy function and the cultural function. The findings indicate that the Indonesian government, in collaboration with non-state actors such as PBESI, the Ministry of Tourism and Creative Economy, and Moonton Games, strategically utilized the M4 World Championship as a platform to advocate Indonesia’s role in the global esports ecosystem and to promote Indonesian cultural elements to international audiences. The integration of cultural diplomacy elements in official events and promotional materials reflects the implementation of the cultural diplomacy function, while institutional narratives and policy support reflect the advocacy function. This study concludes that esport  events such as the M4 World Championship can function as an effective instrument of public diplomacy in enhancing Indonesia’s international engagement and visibility.